2022
DOI: 10.13170/depik.11.3.27723
|View full text |Cite
|
Sign up to set email alerts
|

Reducing ammonia levels in catfish cultivation water using several aquatic plants

Abstract: Catfish farming is one of the businesses that is very much in demand by the community, because it can improve the community's economy. However, not all catfish farming businesses can produce maximum results. This can be caused by several factors, both from feed, management and water quality. Decrease in water quality can be caused by feces and fish feed residue. Poor water quality can cause the growth process, physiology and level of fish behavior to be disturbed. Efforts that can be done is to use aquatic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…The result showed that the value of ammonia produced was 0 to 0.25 mg/L; the results are within the normal range of freshwater fish rearing. Mustaqim et al (2022) stated that the ammonia value for fish rearing should not exceed 1.5 mg/L. The addition of fermented Moringa leaf extract in the feed did not affect the water quality values in the environment for Oranda goldfish.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that the value of ammonia produced was 0 to 0.25 mg/L; the results are within the normal range of freshwater fish rearing. Mustaqim et al (2022) stated that the ammonia value for fish rearing should not exceed 1.5 mg/L. The addition of fermented Moringa leaf extract in the feed did not affect the water quality values in the environment for Oranda goldfish.…”
Section: Discussionmentioning
confidence: 99%
“…Ikan lele memiliki sifat yang sangat adaptif dan tahan terhadap kondisi lingkungan yang berbeda (Jin et al 2016). Ikan ini mampu hidup di perairan dengan kualitas air yang buruk, seperti air yang keruh atau mengandung limbah organic (Mustaqim et al 2022). Ikan lele juga dapat hidup dalam kondisi kekurangan oksigen, sehingga sering dijadikan ikan pilihan dalam budidaya ikan air tawar.…”
unclassified